La Buiatría en la sociedad, un compromiso permanente - Lanuza Ayerdi, Francisco (Revista Colombiana de Ciencias Pecuarias, 2017)
A brief history of the evolution of the diet of man from the domestication of animals to the formation of the World Association of Buiatrics is given in 1962 in Vienna, Austria. At the end of the same decade, the Latin American Association of Buiatrics was formed in 1969 in La Plata, Argentina. This is a trade association of a technical and scientific nature that brings together the different societies and associations of Veterinary Practitioners of the countries of Latin origin in America and the Caribbean, working in the field of Buiatrics (bovines and minor ruminants), to promote and intensify the study of the specialty, to disseminate the results of the researches, both applied and to promote the exchange of experiences. At present, Argentina, Brazil, Chile, Colombia, Costa Rica, Ecuador, México, Paraguay, Perú, and Uruguay participate, having organized 18 Latin American Congresses since 1971, and four countries organized world congresses. Since 2007, the Pablo Videla Prize, founder of the Association, has been presented to a prominent member. The challenges of the Association of Buiatrics are related to the population increase, with an increasing demand for food of animal origin, with changes in eating habits and greater demands of the consumer, associated to the protection of the environment. It is necessary to open roads to be integrated to multidisciplinary teams of professionals in the entire agro-food chain. Welcome to the Buiatrics!